Is it Moving? Arte Programmata on the Screen - Marta Previti (Cinergie)
How to keep track of the movement of a programmed work, real or virtual that it may be? This essay highlights the difficulties that kinetics artists had to face for the mediation of their kinetic or optical-dynamic objects, especially at the beginning of their experimental research. Going through some of the Gruppo N experiences with a new and inedited point of view, this paper intends to identify the link established by those artists with the audiovisual media. This exchange, little investigated so far, comes out from the need to get past the limits of the photographic media, which didn’t fit with the adequate reading of their works.